The nuclear actin-related proteins Arp7 and Arp9: a dimeric module that cooperates with architectural proteins for chromatin remodeling - Szerlong, Heather (Oxford University Press, 2003)
Nuclear actin-related proteins (ARPs) are essential components of chromatin remodeling and modifying complexes, but their functions and relationship to actin remain elusive. The yeast SWI/SNF and RSC complexes contain Arp7 and Arp9, and are shown to form a stable heterodimer with the properties of a functional module. Arp7 and Arp9 rely on their actin-related regions for heterodimerization, and their unique C-termini cooperate for assembly into RSC. We suggest that regulated ARP–ARP (and possibly ARP–β–actin) heterodimerization might be a conserved feature of chromatin complexes. A RSC complex lacking Arp7/9 was isolated that displays robust nucleosome remodeling activity, suggesting a separate essential role for ARPs in the regulation of chromatin structure. A screen for suppressors of arp mutations yielded the DNA bending architectural transcription factor Nhp6, which interacts with RSC complex physically and functionally and shows facilitated binding to nucleosomes by RSC. We propose that Arp7/9 dimers function with DNA bending proteins to facilitate proper chromatin architecture and complex– complex interactions.